Peningkatan Mutu Pembelajaran Melalui Pengawasan Berbasis Digital di Era Society 5.0 - Handayani, Dwi Putri; Juharyanto, Juharyanto; Sunandar, Asep (Universitas Negeri Malang, 2024)
Abstract : Supervision is part of school-specific management. The principal's leadership is essential to understanding the strengths and weaknesses of the school. Therefore, it is necessary to ensure and improve the quality of teaching, especially in schools. Ensuring and improving the quality of education cannot be separated from quality management. Improving quality does not have to be public schools, private schools must also improve the quality of their education to support better education in Indonesia. In this case, quality control measures are always needed. The weak commitment of principals, teachers and lecturers to the implementation of quality assurance and the limited number of competent employees make the school quality assurance system ineffective. Currently, school counseling can be done not only offline, but also online through digital media. The use of digital media requires employees who manage digital media. The purpose of this study is to find out how human resources can be prepared to improve the quality of education with the help of digital counseling in schools. Abstrak : Pengawasan merupakan bagian dari manajemen khusus sekolah. Kepemimpinan kepala sekolah sangat penting untuk memahami kekuatan dan kelemahan sekolah. Oleh karena itu, perlu untuk memastikan dan meningkatkan kualitas pengajaran, khususnya di sekolah. Menjamin dan meningkatkan mutu pendidikan tidak lepas dari manajemen mutu. Meningkatkan kualitas tidak harus sekolah negeri, sekolah swasta juga harus meningkatkan kualitas pendidikannya untuk mendukung pendidikan yang lebih baik di Indonesia. Dalam hal ini, tindakan pengendalian mutu selalu diperlukan. Lemahnya komitmen kepala sekolah, guru dan dosen terhadap pelaksanaan penjaminan mutu serta terbatasnya jumlah pegawai yang kompeten membuat sistem penjaminan mutu sekolah tidak efektif. Saat ini konseling sekolah dapat dilakukan tidak hanya secara offline, tetapi juga secara online melalui media digital. Penggunaan media digital membutuhkan karyawan yang mengelola media digital. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana sumber daya manusia yang dapat disiapkan untuk peningkatan mutu pendidikan dengan bantuan penyuluhan digital di sekolah.